Churchill’s British atomic relations with Malan’s government in South Africa, 1951-1954 - Asuelime E. Lucky (Contree, 2014)
In 1951 Churchill assumed office for the second time as Prime Minister of Britain and renewed the effort to sway once again a Commonwealth sentiment on a Nationalistic DF Malan in their atomic relations. The period marked the beginning of an increased quest for uranium residue for peaceful and military purposes by the principal state actors in the World Wars. It is suggested that Britain used its Commonwealth links with the Union of South Africa to gain an edge in the atomic field for the first decade after the Second World War, and became a gatekeeper through which the United States had to seek authorisation. After consulting multi-archival sources in Britain, Canada and South Africa, I argue against this assertion by Richie Ovendale. The British Commonwealth connection was not so imperative in the late 40s and between 1951 and 1954, It was not so much a Commonwealth instinct that saw to collaboration between Britain and South Africa, but rather Malan’s decision to use its uranium as political leverage, particularly when global attention was shifting to Australia as an alternative uranium supply.